Poetry and cinema: From the time-image to the poetic icon - Alonso González, Mario (Tropelías: Review of Literary Theory and Comparative Literature, 2022)
The aim of the present work is to establish an analogy between the lyric mode of literature and a non-narrative filmic mode. For that purpose, the image-time from Gilles Deleuze’s theory of cinema will be related to the characterization of lyric according to the theory of literature: specifically, its temporality, density of significance and ambiguity. This comparative will take a cognitive turn, as the Buckland’s cognitive theory of cinema will be compared to the cognitive-literary notion of the deictic projection, as well as the mirror neurons, and the creation of the poetic icon (Freeman, 2011a) in cinema will be hypothesized. Finally, this theoretical comparative will be put into practice through the analysis of Terrence Malik’s movie The Tree of Life (2011), which will be explained according to its lyrical characteristics.
Keywords: poetry; lyric; theory of literature; theory of cinema; cognitive science; time-image; poetic iconicity